DBU-Mediated Dimerization: Facile Access to 9,9′-Bifluorenylidenes and Isoindigos - Purahong, Nitchakan; Hongthong, Sakchai; Chotsaeng, Nawasit; Kuhakarn, Chutima; Meesin, Jatuporn (My University, 2023)
The present work describes the 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU)-promoted self-dimerization of 9-chlorofluorenes and 3-chlorooxindoles for the preparation of the corresponding 9,9 -bifluorenylidene and isoindigo derivatives in moderate to good yields of 29 97%. The reactions proceed readily in a short reaction time under mild and metal-free conditions. Scale-up syntheses (5.0 mmol) of selected 9,9 -bifluorenylidene derivatives proceed in decent yields, highlighting the synthetic utility of the reported protocol.
Keywords: 3-chlorooxindoles; 9,9′-bifluorenylidenes; 9-chlorofluorenes; dimerization; isoindigos